Zink Selenide Nanofilms Application in Carbon Monoxide Detection. (2016) - Podgornyi, S.O.; Podgornaya, O.T.; Skutin, E.D.; Demeshko, I.P.; Lukoyanova, O.V.; Fedotova, K.I.
Abstract: The article is aimed at developing innovative primary transducer nanoscale material for semi-conductor sensors and investigating their surface physicochemical properties. Zink selenide nanofilms were obtained by discrete thermal evaporation in vacuum. Adsorption properties of the given material for carbon oxide (II) and oxygen were studied by the piezoquartz microweighing. Zink selenide nanofilms applicability in gas analysis was investigated. Based on the obtained experimental data, CO micro-impurities sensor was developed, the laboratory tests passed successfully.